Oral and Anal Carriage of Streptococcus pneumoniae Among Sexually Active Men With HIV Who Have Sex With Men. (8th October 2021) - Tinggaard, Michaela; Slotved, Hans-Christian; Fuursted, Kurt; Storgaard, Merete; Dröse, Sandra; Somuncu Johansen, Isik; Thorsteinsson, Kristina; Kronborg, Gitte; Lebech, Anne-Mette; Benfield, Thomas
Abstract: People with HIV are at increased risk of pneumococcal disease. We investigate oral and anal carriage rates of Streptococcus pneumoniae by molecular methods among 82 men with HIV who have sex with men (MSM). A questionnaire, oral wash, and anal swab samples were obtained at baseline and 12 months. Oral carriage rates were 32.9% (27/82) at baseline and 41.7% (30/72) at follow-up. Anal carriage rates were 2.4% (2/82) at baseline and 2.9% (2/70) at follow-up. Genogroup 24 was predominant. Results suggest high oral carriage rates of S. pneumoniae among MSM living with HIV. A minority were anal carriers.